Vagal nerve endings in visceral pleura and triangular ligaments of the rat lung. Issue 2 (29th November 2016) - Wang, Feng‐Bin; Liao, Yi‐Han; Wang, Yao‐Chen
Abstract: The inner thoracic cavity is lined by the parietal pleura, and the lung lobes are covered by the visceral pleura. The parietal and visceral plurae form the pleural cavity that has negative pressure within to enable normal respiration. The lung tissues are bilaterally innervated by vagal and spinal nerves, including sensory and motor components. This complicated innervation pattern has made it difficult to discern the vagal vs. spinal processes in the pulmonary visceral pleura. With and without vagotomy, we identified vagal nerve fibres and endings distributed extensively in the visceral pleura ('P'‐type nerve endings) and triangular ligaments ('L'‐type nerve endings) by injecting wheat germ agglutinin‐horseradish peroxidase as a tracer into the nucleus of solitary tract or nodose ganglion of male Sprague–Dawley rats. We found the hilar and non‐hilar vagal pulmonary pleural innervation pathways. In the hilar pathway, vagal sub‐branches enter the hilum and follow the pleural sheet to give off the terminal arborizations. In the non‐hilar pathway, vagal sub‐branches run caudally along the oesophagus and either directly enter the ventral‐middle‐mediastinal left lobe or follow the triangular ligaments to enter the left and inferior lobe. Both vagi innervate: (i) the superior, middle and accessory lobes on the ventral surfaces that face the heart; (ii) the dorsal‐rostral superior lobe; (iii) the dorsal‐caudal left lobe; and (iv) the left triangular ligament. Innervated only by the left vagus is: (i) the ventral‐rostral and dorsal‐rostral left lobe via the hilar pathway; (ii) the ventral‐middle‐mediastinal left lobe and the dorsal accessory lobe that face the left lobe via the non‐hilar pathway; and (iii) the ventral‐rostral inferior lobe that faces the heart. Innervated only by the right vagus, via the non‐hilar pathway, is: (i) the inferior (ventral and dorsal) and left (ventral only) lobe in the area near the triangular ligament; (ii) the dorsal‐middle‐mediastinal left lobe; and (iii) the right triangular ligament. Other regions innervated with unknown vagal pathways include: (i) the middle lobe that faces the superior and inferior lobe; (ii) the rostral‐mediastinal inferior lobe that faces the middle lobe; and (iii) the ventral accessory lobe that faces the diaphragm. Our study demonstrated that most areas that face the dorsal thoracic cavity have no vagal innervation, whereas the interlobar and heart‐facing areas are bilaterally or unilaterally innervated with a left‐rostral vs. right‐caudal lateralized innervation pattern. This innervation pattern may account for the fact that the respiratory regulation in rats has a lateralized right‐side dominant pattern.